CESM1.2.2 model simulations of the historical, RCP4.5 and RCP8.5 periods for the Caspian Sea Catchment Area - Sri Durgesh Nandini-Weiss (PANGAEA, 2020)
The dataset compiles the land 2-meter temperature, precipitation and evaporation for the CESM1.2.2 model versions (1CAM5, 1CAM4 and 2CAM4) as well as datasets for the observational data for each of the above. All the datasets are in monthly long term means from 1979-1999 and in NETCDF format.